Analysis of teachers' digital technology on students' learning quality in islamic cultural history subject at ma al-falaah lekis rejo, oku regency - Dina Nopita Sari; Ibnu Shodik; Danyi Riani (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the effect of teachers’ mastery of digital technology on the quality of student learning in the subject of Islamic Cultural History (SKI) at MA Al-Falaah Lekis Rejo, OKU Regency. The research employed a quantitative approach with an associative design. The population consisted of 164 students, and a total of 62 respondents were selected as the sample using proportionate stratified random sampling with Slovin’s formula. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis was conducted using descriptive statistics and chi-square (χ²) test. The findings indicate that teachers’ mastery of digital technology is at a moderate level, while student learning quality is categorized as high. The chi-square test yielded a value of 30.62, which exceeds the critical value at the 5% (9.94) and 1% (13.28) significance levels, indicating a significant influence between teachers’ digital technology mastery and students’ learning quality. This study highlights that digital technology mastery is a crucial factor in improving the quality of SKI learning. Therefore, continuous professional training for teachers is necessary to optimize digital literacy in the classroom and enhance student learning outcomes.